2D.03: IMPROVING DIAGNOSTIC STRATEGY IN PATIENTS WITH LONG-STANDING HYPERTENSION, CHEST PAIN AND NORMAL RESTING ECG. (June 2015) - Conti, A.; Bianchi, S.; Grifoni, C.; Trausi, F.; Angeli, E.; Paolini, D.; Catarzi, S.; Perrotta, M.E.; Covelli, A.; Renzi, N.; Bertolini, P.; Mazzucchelli, M.
Abstract : Objective: The novel exercise computer-assisted high-frequency QRS-analysis (ex-HF/QRS) has demonstrated improved sensitivity and specificity over the conventional exercise-ST/ECG-segment-analysis (ex-ST/ECG) in the detection of myocardial ischemia. The aim of the present study was to test the implementation in diagnostic value of the ex-HF/QRS in patient with hypertension and chest pain (CP) versus the conventional ex-ST/ECG anlysis alone. Design and method: Patients with long-standing hypertension, CP, normal ECG, troponin and echocardiography were enrolled. All patients underwent the ex-ST/ECG and ex-HF/QRS. A decrease >/=50% of the signal of ex-HF/QRS intensity recorded in two contiguous leads, at least, was considered as index of ischaemia, as ST-segment depression >/=2 mm or >/=1 mm and CP on ex-ST/ECG. Exclusion criteria were QRS duration >/=120 msec and inability to exercise. The end-point was the composite of coronary stenosis >50% or acute coronary syndrome, revascularization, cardiovascular death at 3-month follow-up. Results: Six-hundred thirty-one patients were enrolled (age 61+/-15 y). The percentage of age-adjusted maximal predicted heart rate was 88+/-10 beat-per-minute and the maximal systolic blood pressure was 169+/-22 mmHg. Twenty-seven patients achieved the end-point. On multivariate analysis, both the ex-ST/ECG and ex-HF/QRS were predictors of the end-point. The ex-HF/QRS showed higher sensitivity (88% vs 50%; p = 0.003), lower specificity (77% vs 97%; p = 0.245) and comparable negative predictive value (99% vs 99%; p = NS) when compared to ex-ST/ECG. Receiver operator characteristics (ROC) analysis showed the incremental diagnostic value of the ex-HF/QRS (area: 0.64, 95% Confidence Intervals, CI 0.51–0.77) over conventional ex-ST/ECG (0.60, CI 0.52–0.66) and Chest Pain Score (0.53, CI 0.48–0.59); p = NS on pairwise C-statistic. Conclusions: In patients with long-standing hypertension and CP submitted to risk stratification with exercise tolerance test, the novel ex-HF/QRS shows a valuable incremental diagnostic value over ex-ST/ECG.